Obstacles to Investing Cash Deposits in Islamic Banks - Haider Abd, Researcher. Haneen; Abdulbaqi Yousif, Assist. Prof. Itidal (Basra studies journal, 2024)
The significant importance of banks, particularly Islamic banks, is well-recognized. Islamic banks represent the ideal investment institution for Muslim clients seeking to achieve halal profits without engaging in transactions that are prohibited or hindered by Islamic law. Islam prohibits Muslim clients from participating in transactions considered forbidden from their perspective, which encourages clients to invest in Islamic banks through various means, primarily through cash deposits. However, this process is not without challenges, as obstacles can arise that may hinder this investment. These obstacles are categorized into two types: those related to the nature of the operation and those related to the nature of the banking system. This study analyzes and discusses both types of obstacles, using legal texts from the relevant laws and the practices applied in Islamic banks as references.